Analysis of SALT Fabry-Pérot medium resolution data - Tapsoba, Wendyam Blaise (Department of Astronomy, 2016)
The Southern African Large Telescope Fabry-Pérot interferometer has been used in its medium resolution mode to observe three of 30 galaxies of the MHONGOOSE galaxy sample for which very deep HI observation (typically 200 hours/galaxy) will be obtained with MeerKAT. So optical high spatial resolution of 2 arcsec data of NGC 7361, NGC 7424 and NGC 7793 have been obtained. The major object of this thesis was to test SALT Fabry-Pérot medium resolution data in order to pursue the survey of all the MHONGOOSE sample, and to be able to compare the accuracy of the kinematic results. Through this work, some FORTRAN based routines have been improved and they allow us to compute kinematic maps with good accuracy. Indeed, the velocities measured from the profiles of the Hα emission in the data cube are accurate with the range of 1 km s⁻¹ to 10 km s⁻¹. So, we computed the kinematic maps and the rotation curves of the three galaxies using DiskFit and ROTCUR. For NGC 7361 and NGC 7424 we compared the rotation curves derived by both methods. For NGC 7793 we were also able to compare our results with previous studies.